2023
DOI: 10.3389/fpsyt.2023.1129492
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of an additive informal social network intervention for forensic psychiatric outpatients: results of a randomized controlled trial

Abstract: ObjectivesA supportive social network is associated with better mental health and wellbeing, and less criminal behavior. Therefore, this study examined the effectiveness of an additive informal social network intervention to treatment as usual (TAU) among forensic psychiatric outpatients.Materials and methodsAn randomized controlled trial (RCT) was conducted in forensic psychiatric care, allocating eligible outpatients (N = 102) to TAU with an additive informal social network intervention or TAU alone. Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
1
1
0
Order By: Relevance
“…Next, in line with a recent mixed methods study investigating a group befriending program in patients with severe mental illnesses (Botero-Rodríguez et al, 2021), predominantly positive experiences of participants were found with regard to new social experiences, such as the development of social bonds and social support. In addition, we found that four commonly defined types of social support -informational, emotional, instrumental and companionship support -were recognized by patients and coaches during the informal social network intervention (Langford et al, 1997) In line with the model, these qualitative results could offer an explanation (i.e., working mechanism) for the preliminary quantitative results of the RCT showing positive effects of the informal social network intervention, compared to TAU, on relevant treatment outcomes and criminal behavior in forensic outpatients (Swinkels et al, 2023c). However, it should be noted that the qualitative results (i.e., social bonds and support leading to positive feelings and different perspectives) cannot not be extrapolated to all patients.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Next, in line with a recent mixed methods study investigating a group befriending program in patients with severe mental illnesses (Botero-Rodríguez et al, 2021), predominantly positive experiences of participants were found with regard to new social experiences, such as the development of social bonds and social support. In addition, we found that four commonly defined types of social support -informational, emotional, instrumental and companionship support -were recognized by patients and coaches during the informal social network intervention (Langford et al, 1997) In line with the model, these qualitative results could offer an explanation (i.e., working mechanism) for the preliminary quantitative results of the RCT showing positive effects of the informal social network intervention, compared to TAU, on relevant treatment outcomes and criminal behavior in forensic outpatients (Swinkels et al, 2023c). However, it should be noted that the qualitative results (i.e., social bonds and support leading to positive feelings and different perspectives) cannot not be extrapolated to all patients.…”
Section: Discussionsupporting
confidence: 57%
“…More details about the RCT can be found in our published study protocol ; results are presented elsewhere (Swinkels et al, 2023c). The study was approved by the Medical Ethics Committee of the Amsterdam University Medical Center (NL60308.029.17) and preregistered at the Netherlands Trial Register (NTR7163, date of registration: 16/04/2018).…”
Section: Methodsmentioning
confidence: 99%